ХЕРМЕНЕВТИЧКИТЕ ИМПЛИКАЦИИ НА РОМАНЕСКНИОТ ИНТЕРЕС ЗА ИСТОРИЈАТА - Gorgieva-Dimova, Marija (Philological Studies, 2019)
This text is focused on question about interpretative capacities of the novel, manifested in the frames of certain literary genre – historiographic metafiction. The initial premise of this theoretical elaboration is immanent disposition of historiographic metafiction to include the models and procedures of interpretation within its narrative structure, taking into consideration its double (metainterpretative) orientation towards history/historiography and towards its own literary tradition.